STRATEGI KOMUNIKASI LPM DINAMIKA DALAM MEREKRUT ANGGOTA DI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Asmaul Husnah; Suheri Harahap; Anang Anas Azhar (Lafadz Jaya Publisher, 2023)
This research uses a qualitative descriptive approach method to examine the phenomenon intensively, in detail and in depth with observation, interview and documentation techniques that aim to find out the organization's communication strategy in recruiting members with communication accommodation theory and various conceptual frameworks namely communication strategies, organizational communication strategies and recruitment strategies. The results of the study can be explained that the communication strategy of the LPM Dinamika organization in recruiting members is face to face communication (private face to face and public face to face) by conducting socialization, namely entering new student classes, opening stands around campus and distributing brochures and mediated (private mediated and public mediated) using media intermediaries, the LPM dynamics organization disseminates information through social media and the use of captions in posts, class whatapps groups, and opening question and answer sessions on social media and via chat. In addition, the obstacles that occur in recruiting members are elements related to the organization (changes in registration schedules, permits), habits of finding candidates (personal data, ability or understanding of candidates, ethics and attitudes) and environmental factors (distance 3 campus, time and cost).